2018
DOI: 10.1101/gr.228833.117
|View full text |Cite|
|
Sign up to set email alerts
|

Inherited DNA methylation primes the establishment of accessible chromatin during genome activation

Abstract: For animals, epigenetic modifications can be globally or partially inherited from gametes after fertilization, and such information is required for proper transcriptional regulation, especially during the process of zygotic genome activation (ZGA). However, the mechanism underlying how the inherited epigenetic signatures affect transcriptional regulation during ZGA remains poorly understood. Here, we performed genome-wide profiling of chromatin accessibility during zebrafish ZGA, which is closely related to zy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 58 publications
12
67
1
Order By: Relevance
“…Our results are in agreement with two recent studies reporting that the genetic loss of pou5f3 and nanog, or their knockdown by translation-blocking morpholinos, influences the accessibility of chromatin at sites bound by these factors [25,26]. In contrast to the previously reported preference of Pou5f3 and Nanog to open up distal regions that are DNA methylated [25], we find that Pou5f3, Sox19b and Nanog are also important for regulating chromatin accessibility at promoters of zygotic genes, which are generally hypomethylated. This might explain why a third study [26] found no preference for Pou5f3 and Nanog affecting accessibility at hypermethylated sites.…”
Section: Pou5f3 Sox19b and Nanog Establish Chromatin Accessibilitysupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are in agreement with two recent studies reporting that the genetic loss of pou5f3 and nanog, or their knockdown by translation-blocking morpholinos, influences the accessibility of chromatin at sites bound by these factors [25,26]. In contrast to the previously reported preference of Pou5f3 and Nanog to open up distal regions that are DNA methylated [25], we find that Pou5f3, Sox19b and Nanog are also important for regulating chromatin accessibility at promoters of zygotic genes, which are generally hypomethylated. This might explain why a third study [26] found no preference for Pou5f3 and Nanog affecting accessibility at hypermethylated sites.…”
Section: Pou5f3 Sox19b and Nanog Establish Chromatin Accessibilitysupporting
confidence: 92%
“…Our finding that chromatin accessibility increases during genome activation, especially at promoter and enhancer elements, is consistent with recent studies in Drosophila, zebrafish, Xenopus, mouse and human embryos [4,[10][11][12][13]25,49]. An increase in the number and strength of ATAC-seq peaks over time may either be due to an increase in the number of cells in which specific regions are accessible, or an actual increase in the accessibility of specific regions in all cells of the embryo.…”
Section: Zygotic Genome Activation Is Accompanied By a Dynamic Increasupporting
confidence: 92%
See 2 more Smart Citations
“…Such hypotheses align with theoretical models of epigenetically mediated adaptive plasticity, although further empirical investigations in wild populations are merited (Greenspoon & Spencer, ). Provided that epigenetic patterns are maintained across generations (Colomé‐Tatché et al, ; Joo et al, ; Liu, Wang, Hu, Wang, & Zhang, ; Schmitz et al, ), DNA methylation could be integrated into the working model of ecological speciation with gene flow by mediating gene expression and the optimal phenotype under local conditions (Greenspoon & Spencer, ).…”
Section: Discussionmentioning
confidence: 99%